(untitled) (Physical Culture and Sport: Scientific Perspective, 2022)
The article presents a study of the performance of archers in classification rounds during 2017-2021. The training of athletes is considered a complex and multi-component process, where there are a large number of efforts of the coach and the athlete, which as a whole must comply with the current rules of competitive activity. The purpose of our research was to determine the model performance indicators of male and female archers in the classification rounds of the main competitions of the annual cycle during 2017-2021 (using the example of the Ukrainian Championships). The protocols of athletes’ performances were analyzed and the best results in the qualifying round were highlighted. With the help of theoretical analysis and generalization, the state of research of the object and subject, concretization of the goal was studied. The calendar of competitions of the National Archery Federation, literary sources, research by scientists conducted in recent years regarding the system of competitions in archery and sports in general, and the processes that encourage the improvement of the performance of athletes of different age groups are analyzed. The methods of mathematical statistics created an opportunity to work out the results that occurred on the basis of the methods of mathematical statistics, where the arithmetic mean, deviation and percentages based on the results of the athletes’ performances in the qualifying round of the competition were determined. The analysis of competition protocols made it possible to establish that athletes’ results are quite uneven and are demonstrated under the influence of intense loads. The difference between the best and worst result of the winner among cadets is in the direction of a decrease in the result and is recorded at the level of 18 points, which makes it possible to assert the presence of gaps in training. Female cadets have a reverse trend compared to male cadets, i.e. to an increase in the result of performances at competitions, and it is 10 points.